Management of a Holistic Sleep Healthcare in Selected Malaysian Hospitals - Kiong, Fou Yoom (2023)
Sleep apnea is an under-recognized public health issue and is underdiagnosed in Malaysia. The awareness of sleep disorders is slowly increasing in Malaysia, but the availability of sleep centres remains critically low. A holistic approach to managing sleep healthcare patients is needed to bridge the knowledge gap. Obstructive Sleep Apnea (OSA) remains underdiagnosed and undertreated. OSA does not kill the individual but can cause fatal cardiovascular-related complications such as high blood pressure and stroke. OSA amplifies the risk of multiple health conditions associated with increased morbidity and mortality. There could potentially be more OSA patients in Malaysia based on the 7.1% prevalence of clinically suspected OSA in Malaysia. Practical Information Technology will lead to immediate patient care and outcomes improvement. Big data analytics allow business and clinical models to transform into innovative and efficient care delivery. The low cost of wearables that can detect sleep information is a favourable tool for investigating the sleep architectures of individuals. As of today, the data of sleep diagnostics, sleep therapy and wearables are stored independently and do not interact with each other. The idea of integrating data from sleep diagnostics, sleep therapy and wearables has never been explored nor implemented in Malaysian hospitals. In addition, it has yet to be investigated on the feasibility of the integrated data in improving clinicians' management of sleep health patients holistically. The other problem identified is, sleep medicine knowledge is generally low among medical students and clinicians. Lack of education and training in sleep medicine has resulted in a culture of clinicians with minimal knowledge about sleep disorders. There is a need for a multidisciplinary approach to managing OSA patients. There is a need for clinicians from different specialities to treat the multiple medical conditions that the patient may have. The use of a single platform with integrated sleep data could potentially drive knowledge sharing and knowledge transfer among clinicians. This study employed qualitative research with a focus on phenomenon approach. Interview research technique is adopted for this study. The data analysis revealed that 86% of sleep clinicians agreed that multidisciplinary collaboration is a good practice. The sleep clinicians interviewed for this article agreed that data pooled together would allow them to understand better how they manage their sleep health patients with comorbid diseases plus allowing them to examine undetected correlations and trends between specific variables of interest. Data analytics would provide insights that would improve patient care and assist sleep clinicians in increasing patient awareness. The sleep health patients interviewed unanimously agreed that their sleep health issue has adversely affected their capacity to carry out everyday responsibilities because of their persistent daytime somnolence, poor energy, and insomnia. With the integrated data, the sleep clinicians agreed that they would be able to manage their sleep health patients more holistically. It also enhances the multidisciplinary collaboration among clinicians to look beyond the OSA condition alone, filling the knowledge gap in sleep medicine and allowing a team-based holistic approach to the patient’s condition with diverse expertise in diagnostic and therapeutic techniques challenges.